TALKING TO MACHINES, WRITING THE SELF: A DISCOURSE ANALYSIS OF AI-ENHANCED LITERARY LITERACY AMONG VOCATIONAL STUDENTS - Safii, Muhammad; Hadi, Wisman; Harahap, Muharrina (ppjbsip, 2025)
In the age of digital education, artificial intelligence (AI) has emerged as a promising tool to improve literary literacy, particularly among vocational high school students who often perceive literature as abstract or irrelevant. This study investigates the impact of AI-enhanced learning on students’ engagement with literary texts, reframing the research through a discourse analysis lens. We collected data through interviews and classroom observations at SMK Swasta Al Ma'shum Kisaran, using a qualitative phenomenological method. Students interacted with AI platforms to generate, evaluate, and discuss literary content. While results confirm that AI increased student motivation, improved access to information, and provided personalized feedback, this study extends beyond surface-level outcomes by analyzing how discourse practices shifted during learning. Students described AI as an